Effect of phosphorus fertilization on Pinus taeda L. in Red Oxisol in the region of Telêmaco Borba, Paraná, Brasil - Stahl, James; Angelo, Alessandro Camargo; Schumacher, Mauro Valdir; Souza, Karen Koch Fernades de; Biernaski, Fabricio Antonio (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
Currently the Pinus taeda is the most important species used in forest plantation in the southern region of Brazil, serving as the basis for the timber production chain. The purpose of this study was to evaluate the effect of phosphorus addition to the soil in Pinus taeda plantation at two and seven year olds after planting in clay and sandy clay Red Oxisol in the region of Telêmaco Borba, Paraná. Two field experiments were carried out, one in clay soil and the other in sandy clay soil, in a randomized block design with four replications, in which treatments consisted of increasing doses of phosphorus (0, 50, 75 and 100 kg ha-1 P2O5). The doses of phosphorus were applied in the form of triple superphosphate (46% P2O5) in two lateral hole at 30 days after planting. The available soil phosphorus content was characterized as very low. At two and seven years, the diameter and total height of 20 plants per plot were measured, and volume was calculated by area. The results indicated that the use of phosphate fertilization promoted significant gains in the productivity of Pinus taeda up to seven years in sandy clay Red Oxisol, and the response was linear with maximum production for the dose of 100 kg ha-1 P2O5. For clay Red Oxisol there was no significant response to the use of phosphate fertilization until seven years of age.